Incoherent hybrid subcarrier multiplexed spectral-amplitude-coding optical CDMA system using direct decoding detection technique - Sahbudin, Ratna Kalos Zakiah; Abdullah, Mohamad Khazani; Samad, M. D. A.; Mahdi, Mohd Adzir; Ismail, Maimunah; Mokhtar, Makhfudzah (2007)
This paper presents a hybrid subcarrier multiplexed spectral-amplitude-coding optical code-division-multiple-access (SCM SAC-OCDMA) system. The main purpose of this hybrid technique is used because of its ability to enhance the channel data rate of OCDMA systems. On the other hand, SAC-OCDMA is used because of its ability to eliminate the multiple access interference (MAI) when code sequences with fixed in-phase cross correlation are used. As a result, the hybrid system is robust against interference and is much more spectrally efficient. The sustem utilizes double weight (DW) code that has a weight equal to two. A simple and new detection technique for OCDMA named spectral amplitude direct decoding is proposed. The performance of the hybrid system using the new detection technique is compared with that of balanced detection technique. The results of the experiment simulation show that the proposed new detection technique improves the hybrid system performance significantly.